Ammonia produced by bacterial colonies promotes growth of ampicillin-sensitive Serratia sp. by means of antibiotic inactivation - Cepl, Jaroslav; Blahůšková, Anna; Cvrčková, Fatima; Markoš, Anton (FEMS microbiology letters, 2014)
Volatiles produced by bacterial cultures are known to induce regulatory and metabolic alterations in nearby con-specific or heterospecific bacteria, resulting in phenotypic changes including acquisition of antibiotic resistance. We observed unhindered growth of ampicillin-sensitive Serratia rubidaea and S. marcescens on ampicillin-containing media, when exposed to volatiles produced by dense bacterial growth. However, this phenomenon appeared to result from pH increase in the medium caused by bacterial volatiles rather than alterations in the properties of the bacterial cultures, as alkalization of ampicillin-containing culture media to pH 8.5 by ammonia or Tris exhibited the same effects, while pretreatment of bacterial cultures under the same conditions prior to antibiotic exposure did not increase ampicillin resistance. Ampicillin was readily inactivated at pH 8.5, suggesting that observed bacterial growth results from metabolic alteration of the medium, rather than an active change in the target bacterial population (i.e. induction of resistance or tolerance). However, even such seemingly simple mechanism may provide a biologically meaningful basis for protection against antibiotics in microbial communities growing on semi-solid media.
Keywords: Microbial Sensitivity Tests; antibiotic degradation; Serratia; rezistence na ampicilin; Ampicillin Resistance; ampicillin tolerance; mikrobiální testy citlivosti; Escherichia coli; volatiles; antibakteriální látky; Ammonia; Culture Media; kultivační média; ampicilin; Anti-Bacterial Agents; ammonia; Hydrogen-Ion Concentration; Ampicillin; koncentrace vodíkových iontů; amoniak; Serratia sp.